NADPH oxidase-dependent redox signaling in TGF-β-mediated fibrotic responses - Fan Jiang (Redox Biology, 2014)
Uncontrolled fibrosis in organs like heart, kidney, liver and lung is detrimental and may lead to end-stage organ failure. Currently there is no effective treatment for fibrotic disorders. Transforming growth factor (TGF)-β has a fundamental role in orchestrating the process of fibrogenesis; however, interventions directly targeting TGF-β would have undesired systemic side effects due to the multiple physiological functions of TGF-β. Further characterization of the downstream signaling pathway(s) involved in TGF-β-mediated fibrosis may lead to discovery of novel treatment strategies for fibrotic disorders. Accumulating evidence suggests that Nox4 NADPH oxidase may be an important downstream effector in mediating TGF-β-induced fibrosis, while NADPH oxidase-dependent redox signaling may in turn regulate TGF-β/Smad signaling in a feed-forward manner. It is proposed that pharmacological inhibition of the Nox4 function may represent a novel approach in treatment of fibrotic disorders.